Perilaku Pencegahan Demam Berdarah Dengue di Wilayah Kerja Puskesmas Meuraxa Kota Banda Aceh - Ainul Fadla; Farrah Fahdhienie; Vera Nazhira Arifin (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
DHF is a health problem in tropical climates. This disease can disrupt the function of capillary blood vessels and the blood clotting system, thus increasing the risk of bleeding in sufferers. This study design was a case-control study with 31 cases and 31 controls, totaling 62 respondents. The sampling technique was total sampling, with data collected through questionnaires over 27 days. The results of the univariate analysis showed that most respondents sometimes empty landfills (43.5%), do not cover them properly (58.1%), and do not recycle used items (91.9%). In addition, 79% hang clothes indoors, 69.4% use mosquito repellent, and 79% consider the role of mosquito larvae control teams to be inadequate. Bivariate analysis showed that the behavior of draining (p = 0.001; OR = 13.3) and covering water reservoirs (p = 0.033; OR = 2.6) were significantly associated with the incidence of dengue fever, while recycling used goods (p = 0.162; OR = 0.225), hanging clothes (p = 0.755; OR = 1.215), the use of mosquito repellent (p = 0.409; OR = 1.581), and the role of jumantik (p = 0.119; OR = 2.761) did not show a statistical relationship. Community behavior in implementing 3M Plus plays a role in the incidence of DMF, especially the habit of not draining landfills regularly. Therefore, cross-sectoral cooperation and continuous education are needed between the government, health workers, and the community through mosquito nest eradication activities and routine counseling, so that compliance can be increased and the incidence of DMF can be suppressed.